2020
DOI: 10.3390/life10080130
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of the Black Fungus Cryomyces Antarcticus to High Doses of Accelerated Helium Ions Radiation within Martian Regolith Simulants and Their Relevance for Mars

Abstract: One of the primary current astrobiological goals is to understand the limits of microbial resistance to extraterrestrial conditions. Much attention is paid to ionizing radiation, since it can prevent the preservation and spread of life outside the Earth. The aim of this research was to study the impact of accelerated He ions (150 MeV/n, up to 1 kGy) as a component of the galactic cosmic rays on the black fungus C. antarcticus when mixed with Antarctic sandstones—the substratum of its natural habitat—and two Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 57 publications
2
22
1
Order By: Relevance
“…Nevertheless, a clear correlation between the growth ability and the exposure dose was only shown by colonies exposed without materials and in P-MRS. Additionally, cells exposed in absence of materials exhibited a higher growth ability after exposition to higher doses than cells mixed with OS, P-MRS and S-MRS. This latter result was similar to those found in a previous study, in which dried colonies of C. antarcticus were exposed to accelerated helium ions [29]. The maximum shielding depths of grinded OS, P-MRS and S-MRS were 1.48 g/cm 2 , 1.55 g/cm 2 and 1.53 g/cm 2 , respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, a clear correlation between the growth ability and the exposure dose was only shown by colonies exposed without materials and in P-MRS. Additionally, cells exposed in absence of materials exhibited a higher growth ability after exposition to higher doses than cells mixed with OS, P-MRS and S-MRS. This latter result was similar to those found in a previous study, in which dried colonies of C. antarcticus were exposed to accelerated helium ions [29]. The maximum shielding depths of grinded OS, P-MRS and S-MRS were 1.48 g/cm 2 , 1.55 g/cm 2 and 1.53 g/cm 2 , respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, the production of reactive oxygen species (ROS) from the water absorbing minerals in the OS and the regolith simulants may have differently affected the cells in the distinct sets [32]. Compared to our previous results on the growth of C. antarcticus cells exposed to accelerated helium ions [29], these results showed that the fungus exhibited a lower resistance when directly exposed to the more damaging iron ions (Figure 1), in accordance with the different LET values among helium and iron ions. However, differently from the survival reported after accelerated helium ions in the presence of OS, P-MRS and S-MRS materials, no linear survival trend was reported in this experiment.…”
Section: Discussioncontrasting
confidence: 61%
“…Nevertheless, it has been noted that the P-MRS analogue, because it contains phyllosilicatic minerals or clays, presents high adsorption/absorption properties, with respect to the other substrates. It is likely that some minerals were still present in the purified melanin pigments interfering with the UV-Vis analysis, as reported in Pacelli et al [74]; the presence of minerals may have altered melanin absorbance values at 650 nm, thus explaining the unusual spectral profile with a second large peak around 245 nm. In the context of searching for traces of extinct or extant life on Mars, the melanin concentration results from both P-MRS and S-MRS samples (Table 2) led us to assume that, although the estimation of melanin concentration from fungal colonies in Martian analogue regoliths can be altered by the presence of the soil itself, it is still possible to clearly detect the absorbance of purified melanin pigments, even with the presence of mineral compounds and in irradiated samples (up to 5.5 × 10 5 kJ/m 2 ).…”
Section: Discussionmentioning
confidence: 78%
“…Among the other potential biosignatures investigated, we have focused on melanin pigments (present in all domains of terrestrial life) as they belong to those biomolecule classes (i.e., lipids and biopolymers) that exhibit the highest molecular stability and potential preservation among all organic compounds on Earth, i.e., over timescales of billions of years [2,3], while also being abundant in C. antarcticus cell walls [28] and well-known to be involved in photoprotection [43,73,74]. We used three different approaches to detect the pigments: (i) UV-Vis spectrophotometry; (ii) Raman spectroscopy; (iii) FT-IR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of viable cells of C. antarcticus , on average, was higher in the original substrate, from which this organism was isolated, and in the analogue of lunar regolith, in comparison with analogs of the modern and ancient Martian regoliths [ 29 ]. The effect of irradiation by helium and iron ions on the viability of C. antarcticus during immobilization on the same mineral carriers was studied [ 30 , 31 ]. It was found that the type of mineral matrix affects the indicators of cell viability (colony forming units number, integrity of cell membranes and DNA, enzyme activity), but what conditions provide the best survival of microorganisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%